Peran Guru dalam Menanamkan Nilai-Nilai Demokrasi Melalui Budaya Sekolah - Azhar Sulistiyono (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this reserch is provide an overview of the teacher's role in learning democratic values ​​in elementary school culture in Sidoharjo, Sragen district. The method used in this study was obtained through qualitative descriptive data reduction, data presentation, and conclusion drawing which was carried out in sixth grade elementary schools where researchers collected data through observation, interviews and documents. As a result, the teacher's role is very important, namely instilling democratic values ​​through school culture. introduced democratic values ​​will be more effective. Democratic values ​​that can be applied in schools such as through activities: student-centered learning, freedom in choosing the game, awakening democratic sensitivity of students, democratic classroom management. Based on these data, this study proves that democratic values ​​are very important to be instilled in students. The role of teachers in schools as knowledge transformation institutions is responsible for creating a democratic life.